PENGARUH PENERAPAN SISTEM E-FILLING, PEMAHAMAN INTERNET DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PRATAMA DEPOK CIMANGGIS (Studi pada Kantor Pelayanan Pajak Pratama Kota Depok Cimanggis) - Dipa Teruna Awaloedin; Mahardi Aldi Maulana (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2018)
The purposes of this reseach is to know the effects of assembling of e-filling system, internet understanding, and taxpayers awareness against tax payers compliance at Kantor Pelayanan Pajak Pratama Depok during 2011-2015. The population of this research is the entire actived individual taxpayers who listed at KPP Pratama Depok Cimanggis. Sampling implemented with slovin formula because in this thesis the number of the population are already known the whole of the amount. Based on certain criterias which set by the author, then obtained a total sample amounted to 99 sample which go through to 100 sample. Based on the result of the the research shown that 1) assembling of e-filling system variable has significant effects against the tax payers compliance with determination coefficient as 36.2%. 2) internet understanding has effects against the tax payers compliance with determination coefficient as 21,9%. 3) tax payers awareness variable as effects against the tax payer compliance with determination coefficient as 26,1%. From the result of the regression aware that the whole hypotheses within this research are supported statistically.Key word: assembling of e-filling system, internet understanding, and taxpayers awareness.